Algebra of Functions Having Limit : A Limit Algebra (International Journal of Scientific Research in Science and Technology, 2026)
Let X be a compact Hausdorff topological space. Consider the set of all functions from X to K(R or C) which has limit at each point of X. Then functions of this set are bounded under supremum norm and also forms a Banach algebra.